MiR-17-5p and miR-20a promote chicken cell proliferation at least in part by upregulation of c-Myc via MAP3K2 targeting. Issue 1 (December 2017) - Zhang, Xiaofei; Song, He; Qiao, Shupei; Liu, Jing; Xing, Tianyu; Yan, Xiaohong; Li, Hui; Wang, Ning
Abstract The miR-17-92 cluster has been well studied in mammals but less extensively studied in birds. Here, we demonstrated that miR-17-92 cluster overexpression promoted the proliferation of DF1 cells and immortalized chicken preadipocytes (ICPA-1), and miR-17-5p and miR-20a, members of the miR-17-92 cluster, targeted MAP3K2. Further analysis showed that MAP3K2 overexpression reduced the proliferation of DF1 and ICPA-1 cells and attenuated the promotive effect of the miR-17-92 cluster on cell proliferation. Downstream gene expression analysis of the MAPK signalling pathway showed that MAP3K2 overexpression decreased c-Myc expression; in contrast, MAP3K2 knockdown using RNA interference and miR-17-92 cluster overexpression increased c-Myc expression. Furthermore, c-Myc overexpression promoted miR-17-92 cluster expression and DF1 cell proliferation. Taken together, these data indicated that miR-17-92 promotes chicken cell proliferation at least in part by the upregulation of c-Myc via targeting MAP3K2, and the miR-17-92 cluster, c-Myc and E2F1 form a complex regulatory network in chicken cell proliferation.